NULLITIES IN JURY TRIALS: THE NEED FOR TIMELY OBJECTIONS TO AVOID PRECLUSION (CIPEEX, 2025)
This paper examines the requirement that nullities in jury trials be raised at the proper procedural moment to avoid preclusion, with an emphasis on juror ineligibility and bias (impedimento and suspeição). It is a doctrinal and literature review that compiles scholarship and related decisions in criminal procedure, using databases such as SciELO, to systematize the criteria for occurrence and the correct timing for challenging nullities. The aim is to demonstrate that defects known to the parties must be objected to immediately in open court or during the hearing in which they occur and, when related to the trial, during the trial itself, on pain of forfeiture. The method consisted of analyzing doctrinal and normative sources on jury procedure, including the rule that the draw of jurors is public and held between the fifteenth and the tenth business day prior to the session, which serves as a benchmark for assessing timeliness. The findings indicate that a jury judgment will not be set aside for the participation of ineligible or biased jurors if the issue is not raised at the proper time; accordingly, the conclusion reaffirms that timely challenges are essential to safeguard the regularity of the verdict and to prevent irregular convictions.
Keywords: procedural nullity; jury trial; preclusion; juror ineligibility and bias